2018
DOI: 10.1186/s12881-018-0598-5
|View full text |Cite
|
Sign up to set email alerts
|

The conserved p.Arg108 residue in S1PR2 (DFNB68) is fundamental for proper hearing: evidence from a consanguineous Iranian family

Abstract: BackgroundGenetic heterogeneity and consanguineous marriages make recessive inherited hearing loss in Iran the second most common genetic disorder. Only two reported pathogenic variants (c.323G>C, p.Arg108Pro and c.419A>G, p.Tyr140Cys) in the S1PR2 gene have previously been linked to autosomal recessive hearing loss (DFNB68) in two Pakistani families. We describe a segregating novel homozygous c.323G>A, p.Arg108Gln pathogenic variant in S1PR2 that was identified in four affected individuals from a consanguineo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In the case of S1PR2, in vivo studies in lymphocytes have shown a strict dependence on G 13 (14,15), and endothelial S1PR2 also appears to signal dominantly via G 12 or G 13 (16). Inherited missense mutations in S1PR2 have been identified in patients with hearing impairment, and mice lacking S1PR2 are deaf due to functional defects in auditory and vestibular systems (17,18). Acquired mutations in GNA13 (encoding G 13 ) and S1PR2 were found in germinal center B cell-like diffuse large B cell lymphoma (GCB-DLBCL) by deep sequencing studies (15,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of S1PR2, in vivo studies in lymphocytes have shown a strict dependence on G 13 (14,15), and endothelial S1PR2 also appears to signal dominantly via G 12 or G 13 (16). Inherited missense mutations in S1PR2 have been identified in patients with hearing impairment, and mice lacking S1PR2 are deaf due to functional defects in auditory and vestibular systems (17,18). Acquired mutations in GNA13 (encoding G 13 ) and S1PR2 were found in germinal center B cell-like diffuse large B cell lymphoma (GCB-DLBCL) by deep sequencing studies (15,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Missense mutations in S1PR2 have been found in three families with autosomal recessive hearing impairment (Hofrichter et al, 2018; Santos-Cortez et al, 2016). Intriguingly, for one of these families, all individuals with hearing impairment also had distal limb anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Of the five receptors (S1PR 1−5 ), S1PR 4−5 have much narrower patterns of expression compared to S1PR 1−3 receptors, with ubiquitous expression of S1PR 1 in the brain, kidney, lung, spleen and cardiovascular system (Strub et al, 2010 ; Blaho and Hla, 2014 ). While S1PR 1 regulates immune cell function including lymphocyte egress from lymph nodes (Liu et al, 2000 ; Schwab et al, 2005 ; Sanna et al, 2006 ), S1PR 2 is required for vestibular and auditory systems development (MacLennan et al, 2006 ; Ingham et al, 2016 ; Hofrichter et al, 2018 ), whereas S1PR 3 is required for regulation of heart rate (Forrest et al, 2004 ). Further, S1PR 1−3 receptors play an important role in angiogenesis and vascular permeability (Strub et al, 2010 ).…”
Section: Export Of Intracellular S1p Acceptor Molecules and Their Efmentioning
confidence: 99%